Identification and medical importance of coagulase-negative staphylococci species - Minto, Elaine Cristina Manini; Barelli, Cristiane; Martinez, Roberto; Darini, Ana Lúcia da Costa (São Paulo Medical Journal, 1999)
A total of 126 coagulase-negative staphylococci strains (CNS) were isolated from blood samples and from the intravenous catheters and cerebrospinal fluid of 103 patients admitted to the University Hospital of Ribeirão Preto. Staphylococcus epidermidis (68.2%), S. haemolyticus (11.1%) and S. hominis (3.2%) were the most frequent species. The last two CNS showed greater resistance to antimicrobial agents than S. epidermidis. CNS were the agents of infection in 10.7% of the patients and the agents of intravenous catheter colonization in 18.4% of the cases.